Application of Cord Blood and Cord Blood-Derived Induced Pluripotent Stem Cells for Cartilage Regeneration - Rim, Yeri Alice (Cell Transplant, 2018)
Regeneration of articular cartilage is of great interest in cartilage tissue engineering since articular cartilage has a low regenerative capacity. Due to the difficulty in obtaining healthy cartilage for transplantation, there is a need to develop an alternative and effective regeneration therapy to treat degenerative or damaged joint diseases. Stem cells including various adult stem cells and pluripotent stem cells are now actively used in tissue engineering. Here, we provide an overview of the current status of cord blood cells and induced pluripotent stem cells derived from these cells in cartilage regeneration. The abilities of these cells to undergo chondrogenic differentiation are also described. Finally, the technical challenges of articular cartilage regeneration and future directions are discussed.